2020
DOI: 10.1021/acsomega.0c03742
|View full text |Cite
|
Sign up to set email alerts
|

Method of Predicting the Location of Water Cresting for Horizontal Wells in a Water-Drive Reservoir for Early Prevention

Abstract: A method of prediction of location of water cresting and characterizing its intensity in a horizontal well in a water-drive reservoir is introduced for the first time. A mechanistic model for water cresting derived from Darcy’s equation incorporating the main parameters reported in the literature affecting water cresting—viscosity, well distance to the aquifer, wellbore pressure gradient, and reservoir heterogeneity—is introduced with two new characterizing parameters. First is a model-derived parameter, calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…By physically modeling the key parameters mentioned in this work to a specific target, the test relevancy for the corefloods or petrophysical testing can have very high data relevancy. As a renewable substitute for target formation with tailorable dimensions, this advanced physical model can be cut into different shapes and made into a heterogeneous model by joining sections of different petrophysical properties together for mechanistic studies [37].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…By physically modeling the key parameters mentioned in this work to a specific target, the test relevancy for the corefloods or petrophysical testing can have very high data relevancy. As a renewable substitute for target formation with tailorable dimensions, this advanced physical model can be cut into different shapes and made into a heterogeneous model by joining sections of different petrophysical properties together for mechanistic studies [37].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Based on the reservoir petrophysical data and the wellbore trajectory data, a model coupling both the wellbore and the reservoir seepage flow was established, with the model revised based on the fluid production volume and pressure drop data. 41 Using this model to calculate the pressure distribution in the horizontal wells, the pressure gradient coefficients (R p ) of the horizontal well were thus obtained, where Δp i is the pressure difference of segment i and Δp ̅ is the average pressure difference. After obtaining the above three coefficients, the breakthrough coefficients for each segment of the horizontal wells were calculated according to eq 1 for the seven test wells.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…In addressing this research problem, the authors recently reported a method that used the pressure data along the well, reservoir permeability, and well trajectory data for the calculation of the distribution of the vertical velocities of the water−oil interface along the length of the well to derive a parameter termed the breakthrough coefficient for quantitating the likelihood of water breakthrough along the length of a horizontal well in a series of sophisticated corefloods using synthetic sandstone models with in-situ pressure and saturation monitoring in real-time. 41 Incorporating the fundamental parameters of pressure gradient, thickness of the reservoir layer between well and water−oil contact, viscosity, and permeability variation in the characterization of the watercresting phenomenon by other groups, Fu et al reported a non-logging alternative method for predicting the likely location of water-cresting prior to its actual occurrence and provided a way to characterize its relative intensity. This paper continues from the authors' last report through an application of their reported methodology for a group of seven wells in an oilfield in northeastern China to compare the predicted location of the water-cresting occurrence to that of the actual location by logging results.…”
Section: Introductionmentioning
confidence: 99%